(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This research is based on the global pandemic COVID-19 that was experienced throughout the world, especially Indonesia. The presence of the Covid-19 Virus pandemic has an impact on various fields, one of which is education. Changes in teaching methods and assessments must also be made online. Many learning applications can be used, but not all of these applications already have appropriate and attractive features and facilities to be used as a medium for assessing student performance after the material is delivered by the teacher online. Quizizz online assessment media was chosen because it is considered capable of minimizing the weaknesses that occur when the evaluation is carried out conventionally so that it is more efficient and effective. This study uses a descriptive approach with quantitative methods and qualitative methods. Selected 24 students of class X Multimedia SMK Multi Karya Medan.